Investigation of boiling heat transfer characteristics of R134a flowing in smooth and microfin tubes - Celen, Ali; Cebi, Alican; Dalkilic, Ahmet Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, boiling heat transfer and pressure drop experiments are performed in order to investigate heat transfer enhancement of microfin tube comparing with smooth one. During constant heat flux (10 kW m(-2)) experiments, effect of mass flux (190-381 kg m(-2) s(-1)), saturation temperature (15-22 degrees C) and vapor quality (0.21-0.77) on heat transfer coefficient and pressure drop are investigated. In addition, boiling heat transfer coefficient and frictional pressure drop correlations given in the literature are compared with measured ones. Moreover, the experiments revealed that experimental boiling heat transfer coefficient and total pressure drop of R134a flowing microfin tube are 1.9 and 3.0 times higher than smooth one having the same fin root diameter, respectively. Furthermore, 94 number of heat transfer and pressure drop raw experimental data belonging to the microfin tube are given for researchers to validate their theoretical models.
Keywords: Microfin tube; Boiling heat transfer coefficient; Pressure drop; Heat transfer enhancement; VOID FRACTION MODELS; PRESSURE-DROP; FIN TUBES; HORIZONTAL SMOOTH; VERTICAL TUBE; EVAPORATION; CONDENSATION; R-134A; REFRIGERANTS; R410A; Thermodynamics; Mechanics